2011
DOI: 10.1186/1471-2210-11-2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of rasagiline, its metabolite aminoindan and selegiline on glutamate receptor mediated signalling in the rat hippocampus slice in vitro

Abstract: BackgroundRasagiline, a new drug developed to treat Parkinson's disease, is known to inhibit monoamine oxidase B. However, its metabolite R-(-)-aminoindan does not show this kind of activity. The present series of in vitro experiments using the rat hippocampal slice preparation deals with effects of both compounds on the pyramidal cell response after electric stimulation of the Schaffer Collaterals in comparison to selegiline, another MAO B inhibitor.MethodStimulation of the Schaffer Collaterals by single stim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 38 publications
1
20
0
Order By: Relevance
“…Here we show that rasagiline can directly modulate NMDA receptor composition at synapse and, consequently, its function, by decreasing NR2A at synaptic sites. This is confirmed by a very recent report describing significant decreases of glutamate receptors-mediated signaling in hippocampus, following treatment with rasagiline at similar concentrations (Dimpfel and Hoffmann, 2011). Moreover, recent data reported a critical functional role for NR2A-containing NMDA receptors -and a less crucial role for NR2B-containing NMDA receptors -in the depression of glutamatergic synaptic transmission and evoked dopamine release in striatum (Schotanus and Chergui, 2008;Schotanus et al, 2006).…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Here we show that rasagiline can directly modulate NMDA receptor composition at synapse and, consequently, its function, by decreasing NR2A at synaptic sites. This is confirmed by a very recent report describing significant decreases of glutamate receptors-mediated signaling in hippocampus, following treatment with rasagiline at similar concentrations (Dimpfel and Hoffmann, 2011). Moreover, recent data reported a critical functional role for NR2A-containing NMDA receptors -and a less crucial role for NR2B-containing NMDA receptors -in the depression of glutamatergic synaptic transmission and evoked dopamine release in striatum (Schotanus and Chergui, 2008;Schotanus et al, 2006).…”
Section: Discussionsupporting
confidence: 73%
“…In vitro studies indicated that the neuroprotective activity of rasagiline can be observed at concentrations below the MAO-B inhibition threshold (Weinreb et al, 2010), mainly between 0.1 and 10 μM ( Bar-Am et al, 2005;Dimpfel and Hoffmann, 2011;Weinreb et al, 2007). On these bases, we treated acute corticostriatal and hippocampal slices with rasagiline 0.1 and 1 μM for 2 hours.…”
Section: Concentration-response Curve Of Rasagiline Effect On Moleculmentioning
confidence: 99%
“…An increasing number of molecular biology and pharmacology studies have shown the neuroprotective effects of MAO inhibitors on the prevention and treatment of AD (21,52,53) (Table I) (15,56,57,61,62,112,114,(131)(132)(133)(134)(135)(136)(137)(138)(139)(140)(141)(142)(143)(144). The main neuroprotective mechanisms of MAO inhibitors in AD include the following: i) Improvement of cognitive impairment (50,54,55), where MAO inhibitors correct chemical imbalances in the brain; ii) antioxidant activities and enhancement of iron-chelating activities (56)(57)(58)(59), where chelators can modulate Aβ accumulation, protect against tau hyperphosphorylation and block metal-associated oxidative stress, thereby holding considerable promise as effective anti-AD drugs (145,146); iii) regulation of APP and Aβ expression processing (56,60), for example ladostigil (TV3326), a selective MAO-B inhibitor, which regulates APP translation and processing (114); iv) the selective MAO inhibitors selegiline and rasagiline have been proven to possess neuroprotective activities in cell cultures and animal models of neurodegenerative diseases through the activation of certain signaling pathways, including p42/44 MAPK and PKC (61); v) inhibition of ChE activity by the MAO inhibitor rasagiline (62)(63)…”
Section: Evidence For the Neuroprotective Effect Of Mao Inhibitors In Admentioning
confidence: 99%
“…In order to search for answers it seems appropriate to deal initially with some plant-derived preparations in the order of dilutions of D4-D6, where for sure some molecules are left within the preparation after the dilution procedure. A second reason to get engaged into this matter was the availability of two very sensitive physiological methods used for years to characterize successfully classic synthetic drugs as well as plant derived extracts: Tele-Stereo-EEG for in vivo characterization [1] and hippocampus slice for in vitro characterization [2] [3]. The former methodology provides evidence for in vivo characterization of dose and time dependent drug effects including predictions for clinical use; the latter provides information on concentration dependent effects of water-soluble preparations on physiological transmission of brain electric signals including hints on the mechanisms of action.…”
Section: Introductionmentioning
confidence: 99%